Kritik Moral dalam Antologi Puisi Potret Pembangunan Karya W.S. Rendra - Muhammad Singgih; Septia Uswatun Hasanah; Tri Maya Sari (LPPM STKIP PGRI Bandar Lampung, 2022)
Poetry that is enough to provide moral criticisms, one of which is the stroke poems of W.S. Rendra's pen. His poems were enough to give a scathing critique of his time and to the end of his life. W.S. Rendra in writing his poems dared to launch a considerable criticism of the risk. The purpose of this research is so that the resulting literary works do not deviate from things that endanger the existence of the author. The method used in this study is the qualitative method. Data analysis will be done using the analysis of the contents of the document (content analysis document) namely by recording the important content expressed in the document or archive, but also its implied meaning. That W.S. Rendra's poems containing the value of moral criticism include poems titled poor people, nursery rhymes, spy rhymes, corn rhymes, rhymes of an old man under a tree, and rhymes of girls and masters.